KEBIJAKAN BPJS KESEHATAN DALAM PENJAMINAN BIAYA KECELAKAAN LALU LINTAS TUNGGAL: ANALISIS HUKUM PERDATA ATAS BATASAN TANGGUNG JAWAB DAN SYARAT LAPORAN POLISI - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This article analyses BPJS Kesehatan’s policy on the coverage of costs arising from single-vehicle road traffic accidents, focusing on the limits of liability and the requirement for a police report from a civil law perspective. This study is important because, in practice, the coverage of single-vehicle accidents often gives rise to legal and administrative issues, particularly regarding active membership status, accident classification, relationships with other insurers, and the obligation to submit a police report as the basis for claim verification. Normatively, BPJS Kesehatan provides health insurance within the framework of the National Social Security System and the provisions on Health Insurance set out in Presidential Regulation No. 82 of 2018 and its amendments, whilst the practice of accident coverage indicates that victims of single-vehicle road traffic accidents are, in principle, eligible for coverage provided they meet certain conditions, including that the accident is not a work-related accident and that they are not covered under another insurer’s scheme. This study employs a literature review method using a normative legal approach. The results of the analysis indicate that BPJS Kesehatan’s liability in single-vehicle accidents is limited and conditional, rather than absolute, as it depends on the participant’s active status, the type of accident, and the outcome of administrative verification. In this context, the police report plays a crucial role as an initial verification tool for determining the chronology, cause and classification of the accident, whilst also establishing the authorised insurer responsible for covering the costs of healthcare services. From a civil law perspective, the requirement for a police report can be justified as an instrument of administrative evidence and legal certainty; however, its application must be proportionate so as not to become an obstacle to participants’ rights to access healthcare services. This article emphasises that BPJS Kesehatan’s policies must be implemented with a balance between legal certainty, participant protection and administrative efficiency, so that the objectives of social security in the health sector are achieved.